Transcutaneous electrical nerve stimulation improves lateral ankle sprain (LAS) in rats by regulating the CXCL10/NF-kB signaling pathway: a potential treatment for LAS - Yan Sun; Min Miao; Ran Chen; Yang Zhang; Tang Xun; Di Wu; Zhiqiang Shen (Molecular Biology Reports, 2026)

MCM-41 induced NiCe synergistic constructs Ni-OV-Ce interface for enhanced oxygen transfer in dry methane reforming - Yuanjing Ran; Xing Yi; Daoping Ye; Tao Zhang; Li Lv; Wenxiang Tang; Yan Wang; Zongpeng Zou; Shengwei Tang (Chemical Engineering Journal, 2026)

Deep learning and hyperspectral imaging for non-destructive amino acid detection in live carp fillets - Ying-jie Qi; Yi-Ming Cao; Yan Zhang; Qi Wang; Ran Zhao; Kai-Kuo Wang; Ying-Jie Chen; Xia-Jun Qi; Jiong-Tang Li (Food Research International, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Colletotrichum nymphaeae causes leaf blight in rose-scented Pelargonium in China - Jiabao Wei; Ran Tang; Jicheng Gu; Qiaoxia Shang; Linfang Long; Yan Chen (Journal of Plant Pathology, 2026)

W-induced reconstruction of NiFe (oxy)hydroxides with abundant O-vacancies as efficient electrocatalysts for water oxidation - Zhiqun Bai; Huifang Chen; Weihao Sha; Junru Lin; Jinyuan Miao; Ao Xie; Junqing Pan; Ran Pang; Kai Yan; Pingyu Wan; Yang Tang (Fuel, 2026)

Quantitative Evaluation of Incomplete Stent Apposition in Intracranial Aneurysms Using Optical Coherence Tomography: a Porcine Model Study - Zhuangzhuang Wei; Ji Ma; Zhike Zhang; Shuailong Shi; Shuhai Long; Shaofeng Shui; Lei Yan; Yan Song; Yi Tang; Ye Wang; Jie Yang; Yuncai Ran; et al. (Translational Stroke Research, 2025)

Self-powered broadband underwater optical communication enabled by enhanced donor-acceptor molecular junction in π-conjugated covalent organic framework - Miao Wang; Zhuang Yan; Qinbai Yun; Pei Chen; Ran Qi; Xiaotao Zhang; Kuo Yuan; Zhiyong Tang; Wenping Hu (Chemical Engineering Journal, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Progressive failure mechanism of water glass modified recycled rock-filled concrete based on radon monitoring and resistivity monitoring - Cheng Hua; Xiaochun Lu; Ran Tang; Tao Luo; Niankui Peng; Tao Yan (Engineering Structures, 2025)

Corrigendum to “Neovascularization-directed bionic eye drops for noninvasive renovation of age-related macular degeneration” [Chem. Eng. J. 450 (2022) 138291] - Meixin Ran; Yaxin Deng; Jiaqi Yan; Anan Zhang; Ying Wei; Xiaowen Li; Haibing He; Jingxin Gou; Tian Yin; Xing Tang; Jun Kong; Han Zhang; et al. (Chemical Engineering Journal, 2025)

Distribution Range and Richness of Plant Species Are Predicted to Increase by 2100 due to a Warmer and Wetter Climate in Northern China - Ying Sun; Yan Deng; Shuran Yao; Yuan Sun; Abraham Allan Degen; Longwei Dong; Jiali Luo; Shubin Xie; Qingqing Hou; Dong Tang; Yuzhen Sun; Junlan Xiong; et al. (Global Change Biology, 2025)
The warming global climate is threatening terrestrial ecosystem stability, including plant community structure and diversity. However, it remains unclear how distribution, richness, and turnover of plant species are impacted by warming and wetting in northern China. In the present study, species distribution models were applied to predict the spatial distribution of 5111 plant species based on 111,071 occurrence records in northern China. Additionally, variations in species richness and turnover rates were predicted for 2100 under 3 scenarios. The results indicated that approximately 70% of plant species will expand in their distribution, resulting in an increase in species richness. These changes will be driven mainly by temperature seasonality (TSN), annual precipitation (MAP), and mean temperature of the coldest quarter (MTCQ). However, about 30%–40% of the species will face extinction risks, including a considerable number of endemic and Red‐Listed species, and suitable habitat loss (LSH) will exceed 30%. Narrow‐ranging species will be more likely to lose a larger percentage of their suitable habitats than wide‐ranging species, highlighting their sensitivity to environmental changes. Importantly, it emerged that species turnover rates will increase linearly with ecological vulnerability at the grid level, indicating that community structure and species composition are easily affected by climate change in ecologically vulnerable areas. Therefore, biodiversity hotspots with high species richness in the southern study areas, as well as regions exhibiting both fast species turnover and significant ecological vulnerability, should be prioritized for conservation. These findings provide insights into how species composition and richness in plant communities vary with global climate change and provide effective ecological conservation and management strategies.

Simultaneous extraction and in situ separation of flavonoids and alkaloids from mulberry leaves using a pH-responsive deep eutectic solvent/water system - Ruili Ma; Weiguo Wu; Yikang Shu; Ran Gao; Ziyu Wang; Daoquan Tang; Yan Du; Shuai Ji (Food Chemistry, 2025)

Nitrate ameliorates myelin loss and cognitive impairment in Alzheimer’s disease through upregulation of neuronal sialin and subsequent inhibition of TPPP phosphorylation - Xinyue Chen; Geng Hu; Lirong Chang; Xiaoyu Li; Yi Tang; Yan Wu; Ran Zhang; Chunmei Zhang; Jinsong Wang; Xue Wang; Songlin Wang (Science Bulletin, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Corrigendum to “Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing” [Carbohydr. Polym. 343 (2024) 122492 - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2025)

Meniscal scaffolds based on self-healable elastomer-hydrogel composites with biomimetic structure and tribological properties for repairing meniscal injuries - Feng Tian; Wenqiang Yan; Manwen Zhang; Lingyu Zhao; Zeyuan Gao; Xiaoqing Hu; Jin Cheng; Shimin Xu; Lei Tang; Yingfang Ao; Wei Huang; Ran Yu (Chemical Engineering Journal, 2024)

Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Visual environment in schools and student depressive symptoms: Insights from a prospective study across multiple cities in eastern China - Xiyan Zhang; Jiawen Tang; Yan Wang; Wenyi Yang; Xin Wang; Ran Zhang; Jie Yang; Wei Lu; Fei Wang (Environmental Research, 2024)

Customization of indium-based MOFs for enhanced adsorptive and photocatalytic of organic pollutants: Morphology involvement on performance and mechanism - Wenliang Zhang; Yan Wang; Timing Fang; Xiao Tang; Zhezheng Ding; Yunhai Han; Ran Guo; Pengfei Qi; Xiaomin Liu (Chemical Engineering Journal, 2024)

Modulating ferroptosis for the prevention of urinary stone recurrence: An innovative strategy employing Tetrahedral Framework Nucleic acids and Polydatin conjugates - Shijian Feng; Ran Yan; Cai Tang; Zhaofa Yin; Bohan Liu; Pengan Chen; Yushi He; Liang Zhou; Yunfeng Lin (Chemical Engineering Journal, 2024)

Assessing the modulation of outer bank erosion by slump blocks: A case study from Marqu Meadow, China - Lei Liu; Lekui Zhu; Dong Chen; Qihua Ran; Honglei Tang; Jun Yan; Lin Liu (Geomorphology, 2024)

Engineering of molecularly imprinted cavity within 3D covalent organic frameworks: An innovation for enhanced extraction and removal of microcystins - Yu-Hong Tang; Tian-Tian Ma; Xu-Qin Ran; Yukun Yang; Hai-Long Qian; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

Study on the mechanism of arsenic-induced renal injury based on SWATH proteomics technology - Xiaolu Chen; Xi Yan; Xiaoxiao Tang; Yi Wang; Xinglai Zhang; Xueshan Cao; Xiaoqian Ran; Guanwei Ma; Ting Hu; Ayesha Qureshi; Peng Luo; Liming Shen (Journal of Trace Elements in Medicine and Biology, 2024)

Insights on the NF-κB system in polycystic ovary syndrome, attractive therapeutic targets - Wei Tan; Jie Zhang; Fangfang Dai; Dongyong Yang; Ran Gu; Lujia Tang; Hua Liu; Yan-xiang Cheng (Molecular and Cellular Biochemistry, 2024)

A new framework for multi-level territorial spatial zoning management: Integrating ecosystem services supply-demand balance and land use structure - Yifei Xu; Xiaoqing Zhao; Pei Huang; Junwei Pu; Yuju Ran; Shijie Zhou; Qiaoqiao Zhao; Yan Feng; Yuanyuan Tang; Junyi Tao; Yangbin Zhang (Journal of Cleaner Production, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Development of an LC-MS/MS method for the determination of multiple mycotoxins in human urine - Mobing Chen; Wei Liu; Ping Xiang; Linhao Xu; Yiling Tang; Ran Kong; Shuo Yang; Hui Yan; Bin Di (Food Additives & Contaminants: Part A, 2023)

Source apportionment of nitrate in the Pearl River Estuary using δ15N and δ18O values and isotope mixing model - Ran Long; Fei Tian; Jian-hua Chen; Yan-bo Zhou; Xue-fei Li; Yi-tong Li; Hai-wei Tang; Hai-gang Chen (Marine Pollution Bulletin, 2023)

Terrigenous organic carbon contributes to reservoir carbon emissions: Potential role of the microbial community along a trophic gradient - Qiong Tang; Lunhui Lu; Fang Luo; Xinrui Li; Yuanyuan Zhang; Ran Li; Carolina Bernal; Solange Vera; Irina Izaguirre; Yan Xiao; Zhe Li (Journal of Hydrology, 2023)

The pH dependence of photochemical reactions between methoxyphenols with Fe(III)-oxalates - Wangjin Yang; Jiawei Ma; Xiangli Nan; Ran Yan; Ning Tang; Tao Du; Chong Han (Atmospheric Environment, 2023)

Molecular phylogenetics and population demographic history of Amphioctopus fangsiao, inferred from mitochondrial and microsatellite DNA markers - Jian Zheng; Yan Tang; Ran Xu; Xiaoying Zhang; Xiaodong Zheng (Acta Oceanologica Sinica, 2023)

Three new constituents from the Tujia ethnomedicine Swertia punicea Hemsl. - Pan Yi; Bin Li; Salman Zafar; Sajjad Ali; Wen-Bing Sheng; Yu Mao; Fang Zhou; Wen-Ming Chen; Yan-Ran Tang; Cai-Yun Peng; M. Iqbal Choudhary; Atta-ur- Rahman; et al. (Natural Product Research, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

Sulfadiazine oxidation by peroxodisulfate and cobalt loaded graphitic biochar system: The dominant role of graphitic domain - Qiuhui Zhu; Kaixuan Guo; Shuanglong Ma; Shulian Wang; Xiaodan Tang; Ran Duan; Yan Huang; Jingzhen Wang; Gong Cheng; Shengjun Xu; Xuliang Zhuang (Chemical Engineering Journal, 2023)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

DNA Barcoding Reveals High Hidden Species Diversity of Chinese Waters in the Cephalopoda - Ran Xu; Yuhan Lü; Yan Tang; Zhiwei Chen; Chenxi Xu; Xiaoying Zhang; Xiaodong Zheng (Frontiers in Marine Science, 2022)
Species delimitation by traditional morphological methods is challenging in cephalopods due to their flexible bodies, changeable pigment traits, and sometimes high morphological homoplasy. Molecular information provides important assistance for taxonomic decision. In this study, we applied three species delimitation methods on 132 cephalopods from 7 families along Chinese waters, and we found anunderestimated species diversity in these taxa. A maximum of 56 molecular operational taxonomic units was detected, and possible cryptic diversities were revealed in Loliolus beka , Uroteuthis edulis , Octopus minor , Amphioctopus fangsiao , and Hapalochlaena lunulate . This study provides molecular evidence for the hidden species diversity along Chinese waters, and it provides insight into further taxonomic research on these morphologically variable taxa.

Transcriptome sequencing and analysis for the pigmentation of scale and skin in common carp (Cyprinus carpio) - Yu-Jie Zhao; Jun Xiao; Mei-Di Huangyang; Ran Zhao; Qi Wang; Yan Zhang; Jiong-Tang Li (Molecular Biology Reports, 2021)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Building a sequence map of the pig pan-genome from multiple de novo assemblies and Hi-C data - Xiaomeng Tian; Ran Li; Weiwei Fu; Yan Li; Xihong Wang; Ming Li; Duo Du; Qianzi Tang; Yudong Cai; Yiming Long; Yue Zhao; Mingzhou Li; et al. (Science China Life Sciences, 2020)

Pesticides in three rural rivers in Guangzhou, China: spatiotemporal distribution and ecological risk - Xiao-Yan Tang; Yang Yang; Nora Fung-Yee Tam; Ran Tao; Yu-Nv Dai (Environmental Science and Pollution Research, 2019)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Biosorption and degradation of decabromodiphenyl ether by Brevibacillus brevis and the influence of decabromodiphenyl ether on cellular metabolic responses - Linlin Wang; Litao Tang; Ran Wang; Xiaoya Wang; Jinshao Ye; Yan Long (Environmental Science and Pollution Research, 2016)

Calmodulin kinase II inhibitor regulates calcium homeostasis changes caused by acute β-adrenergic receptor agonist stimulation in mouse ventricular myocytes - Yan Huang; Tao Liu; Dandan Wang; Xin Wang; Ran Li; Yuting Chen; Yanhong Tang; Teng Wang; Congxin Huang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Scaffold-based design of xanthine as highly potent inhibitors of DPP-IV for improving glucose homeostasis in DIO mice - Yan Ran; Heying Pei; Caifeng Xie; Liang Ma; Yuzhe Wu; Kai Lei; Mingfeng Shao; Minghai Tang; Mingli Xiang; Aihua Peng; Yuquan Wei; Lijuan Chen (Molecular Diversity, 2015)

Heat shock factor OsHsfB2b negatively regulates drought and salt tolerance in rice - Jianhua Xiang; Jing Ran; Jie Zou; Xiaoyun Zhou; Ailing Liu; Xianwen Zhang; Yan Peng; Ning Tang; Guangyu Luo; Xinbo Chen (Plant Cell Reports, 2013)

Polymorphisms of KiSS-1 and GPR54 genes and their relationships with litter size in sheep - Mingxing Chu; Chaoting Xiao; Tao Feng; Yan Fu; Guiling Cao; Li Fang; Ran Di; Qianqian Tang; Dongwei Huang; Yuehui Ma; Kui Li; Ning Li (Molecular Biology Reports, 2012)